Gendered Narratives and Linguistic Force Dynamics: Influencing Career Paths of Women - Amna Iqbal; María Isabel Maldonado García (JISR Management and Social Sciences & Economics, 2020)
This paper examines the career choice narratives and their possible impact on female adolescents’ career constructs and academic aspirations in the Kasur district. The study presumes that narratives, integrated with socio-economic factors have the potential to influence career trajectories of female youth. Considering language structure as central to the system of interaction (Giddens, 1986), it takes Cognitive linguistic approach to CDA (Hart, 2014) and analyses how linguistic force-interactive patterns can influence female students’ career self-efficacy beliefs, outcome expectations and goals. The results reveal that social actors, with their linguistic choices, become a source of enablement or dissuasion for females’ career path. The research allowed young women to voice their feelings and remove barriers to better understanding their academic/professional competence; the findings are helpful to contextualize career guiding discourse.